PENDAMPINGAN PEMBANGUNAN PONDASI JEMBATAN SEBAGAI AKSES PERUMAHAN PERMATA JANGLI TAHAP 2 - Sulistiawati, Baiq Heny; Pangesti, Rendy Dwi; Supriyadi, Supriyadi; Fatmawati, Leily; Rahmawati, Roselina; Setyono, Karnawan Joko; Sukoyo, Sukoyo; Mulyono, Tedjo; Sudarmono, Sudarmono; Warsiti, Warsiti (Bangun Rekaprima, 2024)
Bridges have a central role as routes that connect between regions, one of which is Permata Jangli Housing Phase 2. Because of the importance of this connectivity, community dedication to repairing bridges is a major concern in efforts to maintain the safety and sustainability of the bridge. This community service examines repair methods for the retaining walls around the bridge to avoid the potential for the bridge to be eroded by water flow. Through the active participation of community members and the implementation of appropriate construction techniques, the results of this collaboration show that the retaining walls around the bridge have been successfully repaired, as well as increasing their resistance to water pressure and erosion. The success of this community service not only improves the quality of life of local residents by ensuring sustainable connectivity, but also empowers communities in efforts to preserve their vital infrastructure. This community service can be an inspiring example for similar efforts in similar housing complexes that face similar challenges in maintaining important infrastructure such as bridges. This underlines the important role of community service in maintaining infrastructure as a key aspect in sustainable development in urban housing.